Pengaruh Komitmen Organisasi, Budaya Organisasi dan Kepuasan Kerja terhadap Kinerja Karyawan Hotel Grand Rocky Bukittinggi - Vebriasih Fertika; Arif Adrian (Jurnal bintang manajemen, 2025)
This research aims to determine the influence of organizational commitment, organizational culture and job satisfaction on the performance of Grand Rocky Bukittinggi hotel employees. The research used is a sampling technique using an associative approach in the form of a causal relationship of quantitative descriptive type. In collecting data, the technique used was distributing questionnaires to 99 respondents whose validity and reliability had been tested using a Likert scale. The analytical tool used is multiple linear regression. The techniques used in analyzing the data are data description, testing analysis requirements through normality, heteroscedasticity and multicollinearity tests assisted by SPSS v.25. The results of this research are that Organizational Commitment is classified in the sufficient category through a respondent achievement level of 3.22%, for Organizational Culture it is classified in the sufficient category through a respondent achievement level of 3.35%, then for Job Satisfaction it is classified in the sufficient category through a respondent achievement level of 3, 13%, and employee performance is in the sufficient category with a respondent achievement level of 3.35%. The contribution of Organizational Commitment (X1), Organizational Culture (X2) Job Satisfaction (X3) and Employee Performance (Y) is 13.5% while the remaining 86.5% is influenced by other factors.